Typification of the first recognized blue pigmented diatom, Haslea ostrearia (Bacillariophyceae) - Michel Poulin; Vona Méléder; Jean-Luc Mouget (Plant Ecology and Evolution, 2019)
Background and aims – The blue pigmented diatom, Haslea ostrearia (Gaillon) Simonsen, which has been the material object for many physiological and ecological studies, was first described from oyster ponds in France as Vibrio ostrearius Gaillon; however, his study material seems not to be conserved.Methods – A thorough search to retrieve potential available historical collections has been conducted.Key results – It has been proven that no relevant historical material exists for H. ostrearia. Thus, an oyster pond at Bouin in Baie de Bourgneuf, France, was sampled in 2018 to obtain material allowing neotype designation.Conclusion – Slides and stubs have been deposited as neotype material of the species in the Muséum National d’Histoire Naturelle, Paris, France (PC). At the same time, this material is the generitype of the genus Haslea Simonsen. Furthermore, isoneotypes have been deposited at the British Museum (BM) and the Bremerhaven Hustedt collection (BRM).